KONSEP PEMERINTAHAN BAKRI SYAHID DALAM TAFSIR AL-HUDA TAFSIR QUR’AN BASA JAWI - Zaelani, Thoriq Fadli (Living Islam: Journal of Islamic Discourses, 2022)
Abstract Government is important in carrying out a life in the nation and state, in order to achieve the welfare of the world and the hereafter, both materially and spiritually. This study aims to examine the concept of government according to Bakri Syahid in Al-Huda's interpretation and to reveal how Bakri Shahid interprets the government verses. The method used is the description method in which the researcher describes regularly the thought conception of the character, including the biography of the character and the theory of literary interpretation of the Qur'an (al-tafsîr al-adabî li al-Qur’an) as a knife of analysis initiated by Amîn al-khûlî. The results of this study prove that there are five main concepts of government according to Bakri syahid in Al-Huda's interpretation, these concepts are: the concept of divinity, the concept of humanity, the concept of unity, the concept of deliberation and the concept of justice. However, in interpreting the verses of Bakri Shahid's government, he was greatly influenced by his scientific and professional background, as well as the influence of the social and cultural background of his time. Keywords: government; interpretation; justiceAbstrak Pemerintahan merupakan hal yang penting dalam menjalankan suatu kehidupan dalam berbangsa dan bernegara, demi tercapainnya kesejahteraan dunia maupun akhirat, baik dalam matrial maupun sepiritual. Penelitian ini berupaya untuk mengkaji konsep pemerintahan menurrut Bakri Syahid dalam tafsir Al-Huda dan untuk mengungkap bagaimana penafsiran Bakri Syahid terhadap ayat-ayat pemerintahan. Metode yang digunakan adalah metode deskripsi dimana peneliti menguraikan secara teratur konsepsi pemikiran dari tokoh, termasuk di dalamnya adalah biografi dari tokoh tersebut dan teori tafsir sastra terhadap al-Qur’an (al-tafsîr al-adabî li al-Qur’an) sebagai pisau analisanya yang digagas oleh Amîn al-khûlî. Hasil penelitian ini membuktikan bahwa, ada lima pokok yang menjadi konsep pemerintahan menurut Bakri syahid dalam tafsir Al-Huda, konsep-konsep tersebut adalah: konsep ketuhanan, konsep kemanusiaan, konsep persatuan, konsep musyawarah dan konsep keadilan. Sedangkan dalam  menafsirkan ayat-ayat pemerintahan  Bakri Syahid sangat dipengaruhi oleh latar belakang keilmuan dan profesi yang ia jalani, serta pengaruh dari latar belakang kehidupan sosiaal dan budaya pada masa nya. Kata Kunci: pemerintah; tafsir; keadilan